Interrelations of quantitative and qualitative characteristics of productivity of the new peas lines - A. R. Ashiev; K. N. Khabibullin; M. V. Skulova; D. P. Dorokhova (Зерновое хозяйство России, 2019)
In 2016-2018 in the competitive variety testing there was conducted the study of peas on the fields of research crop rotation of the laboratory of legumes breeding and seed-growing of the FSBSI “ARC “Donskoy” located in the zone of unstable humidity of the Rostov region (Zernograd district). The analysis of the obtained seeds was carried out in the laboratory of biochemical estimation of breeding material and grain quality of the FSBSI “ARC “Donskoy”. The objects of research were new pea lines of breeding of the FSBSI “ARC “Donskoy”, which differed in their morphological, biological and economically valuable traits and properties. During the years of research, the meteorological conditions of the vegetation period of peas were contrasting, which made it possible to objectively estimate the lines in the climatic conditions. In the competitive variety testing for the period of 2016-2018, the evaluation of new promising pea lines due to their productivity and protein percentage resulted in identification the leafless pea lines “G-1002” and “G-1003” which exceeded the standard variety “Aksaisky Usaty 5” in productivity (0.30 and 0.39 t/ha) and protein yield (0.08 and 0.10 t/ha, respectively). There is a high correlation between seed productivity and protein content (0.95). There is a low correlation between protein percentage in seeds and protein yield (0.35). There is no correlation between productivity and protein percentage in seeds (0.03). The analysis of correlations shows that pea breeding on productivity directly affects on protein yield, i. e. the larger seed productivity, the larger protein percentage. The most productive pea lines are going to be used in further breeding work.